Future broadband radio access systems for integrated services withflexible resource management. - Tjelta, T. (IEEE Communications magazine)
The current challenge in radio networks is to provide integrated broadband services to everybody. The realization of this goal is dependent on both the development of products for the mass market and the improvement of the systems that support these products. New cellular mobile, fixed terrestrial, and satellite systems are being developed to provide broadband integrated services. The users of these new systems will not need, or even want, to know which particular systems are used to access the requested services. The users may negotiate terms of delivery, such as data rate and quality of service, but the actual system of delivery should be transparent. In order to both achieve transparent service delivery and ensure efficient use of the radio frequency spectrum, a flexible and scaleable resource management system is needed. This article highlights the development trends that will form the basis of future network systems and presents some suggestions for the management and control of these systems